2020
DOI: 10.1097/upj.0000000000000167
|View full text |Cite
|
Sign up to set email alerts
|

Tele-Urology During COVID-19: Rapid Implementation of Remote Video Visits

Abstract: Introduction: COVID-19 has brought unprecedented challenges to the delivery of urological care. Following rapid implementation of remote video visits at our tertiary academic medical center serving a large rural population we describe and assess our experience with planned video visits and ongoing scheduling efforts.Methods: Patients scheduled for video visits between April 14 and April 27, 2020 were included. Prospective and retrospective data were collected on patient and clinical characteristics as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…The summary of analysis is provided in Table 3, which lists the themes/observations from reviewers that correspond with the objective statement and sorts articles from the most recent to the oldest. [25] Not reported Convenience of telemedicine, increased patientprovider communication, concerns adequately addressed, increased access Strong satisfaction Richards et al [24] Some patients prefer in-person consultations, technical literacy Pandemic created acceptance of technology, past experience with technology Not reported Kurihara et al [23] Technology needs further development, technical literacy Technical literacy, past experience with technology, perceived usefulness, increased patient-provider communication, perceived ease of use Not reported Alkirie et al [26] Technology needs further development Increased connectedness, self-management, flexibility, and access Not reported Ballin et al [27] Health literacy, availability of technology, technical literacy Enabled social interaction; decreased anxiety; increased connectedness, technical literacy, and access; televideo enables reading of body language; education; convenience of telemedicine Not reported Banbury et al [28] Technology needs further development, decrease in patient-provider communication, technical literacy, confidentiality/security Increased efficiency, access, and patient-provider communication, and improved standard of care Not reported Barnett et al [29] Discomfort for wearable monitors, technical literacy, technology needs further development Technical literacy, increased self-management, increased access, increased flexibility Not reported Batalik et al [30] Limits of reimbursement for telemedicine, some patients prefer in-person consultations, connectivity, technical literacy Pandemic created acceptance of technology, availability of technology, fewer miles driven to appointment, convenience of telemedicine, faster initiation of treatment, decreased costs Not reported Beller et al [31] Perceived lack of usefulness, lack of personal desire to get better, some patients prefer inperson consultations Increased connectedness, increased adherence, improved health behaviors Not reported Bernabe-Ortiz et al [32] Not reported Pandemic created acceptance of technology Not reported Bilgrami et al [33] Decrease in quality of life after intervention Perceived usefulness, perceived ease of use, increased adherence Strong satisfaction Broers et al [34] Technical literacy, availability of technology Increased adherence, increased self-management, increased weight loss, technical literacy Not reported Cho et al [35] Technology needs further development Technical literacy, perceived ease of use Not reported Claes et al [36] Lack of personal desire to get better, technology needs further development, technical literacy Increased adherence, increased self-management Not reported Coorey et al [37] Technology needs fur...…”
Section: Thematic Analysis Based On Results Of Individual Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…The summary of analysis is provided in Table 3, which lists the themes/observations from reviewers that correspond with the objective statement and sorts articles from the most recent to the oldest. [25] Not reported Convenience of telemedicine, increased patientprovider communication, concerns adequately addressed, increased access Strong satisfaction Richards et al [24] Some patients prefer in-person consultations, technical literacy Pandemic created acceptance of technology, past experience with technology Not reported Kurihara et al [23] Technology needs further development, technical literacy Technical literacy, past experience with technology, perceived usefulness, increased patient-provider communication, perceived ease of use Not reported Alkirie et al [26] Technology needs further development Increased connectedness, self-management, flexibility, and access Not reported Ballin et al [27] Health literacy, availability of technology, technical literacy Enabled social interaction; decreased anxiety; increased connectedness, technical literacy, and access; televideo enables reading of body language; education; convenience of telemedicine Not reported Banbury et al [28] Technology needs further development, decrease in patient-provider communication, technical literacy, confidentiality/security Increased efficiency, access, and patient-provider communication, and improved standard of care Not reported Barnett et al [29] Discomfort for wearable monitors, technical literacy, technology needs further development Technical literacy, increased self-management, increased access, increased flexibility Not reported Batalik et al [30] Limits of reimbursement for telemedicine, some patients prefer in-person consultations, connectivity, technical literacy Pandemic created acceptance of technology, availability of technology, fewer miles driven to appointment, convenience of telemedicine, faster initiation of treatment, decreased costs Not reported Beller et al [31] Perceived lack of usefulness, lack of personal desire to get better, some patients prefer inperson consultations Increased connectedness, increased adherence, improved health behaviors Not reported Bernabe-Ortiz et al [32] Not reported Pandemic created acceptance of technology Not reported Bilgrami et al [33] Decrease in quality of life after intervention Perceived usefulness, perceived ease of use, increased adherence Strong satisfaction Broers et al [34] Technical literacy, availability of technology Increased adherence, increased self-management, increased weight loss, technical literacy Not reported Cho et al [35] Technology needs further development Technical literacy, perceived ease of use Not reported Claes et al [36] Lack of personal desire to get better, technology needs further development, technical literacy Increased adherence, increased self-management Not reported Coorey et al [37] Technology needs fur...…”
Section: Thematic Analysis Based On Results Of Individual Studiesmentioning
confidence: 99%
“…Occurrence, n (%) References Themes/observations 12 (9.1) [27,30,35,37,38,40,41,45,46,49,57,58] Increased self-management 11 (8.3) [23,25,31,33,41,43,47,51,52,61,62] Pandemic created acceptance of technology 10 (7.6) [32,34,35,37,38,40,43,46,58,67] Increased adherence 9 (6.8) [24,[27][28][29][30]41,52,53,60] Increased access 8 (6.1) [49,50,54,55,[62][63][64]66] Increased social support 7 (5.3) ...…”
Section: Table 4 Facilitator Themes and Individual Observations (N=132)mentioning
confidence: 99%
See 2 more Smart Citations
“…The rapid scale-up of TM during the COVID-19 pandemic may have long-term implications for access to both general and subspecialty care in SSA. As more health providers are trained and more facilities equipped with TM infrastructure, these services will likely continue to be offered beyond the pandemic ( Beller et al., 2020 ). TM may offer several benefits for health systems in SSA including providing expanded access to services, fostering the integration of rural primary care and remote subspecialty services, and enabling more effective care management ( Bali, 2018a ).…”
Section: Barriers To Full Scale Implementation Of Tmmentioning
confidence: 99%